Cyprus - Krambia-Kapardis, Maria; Neophytidou, Christina (My University, 2017)
Each country chapter of this volume provides an overview of the national lobbying industry, taking into consideration also institutional, historical and cultural variables, and placing the analysis of lobbying and public affairs into a wider picture. A short overview of the country’s political system is given, illustrating the institutional structure, the party system or the weight of particular political actors. In order to describe the features of the lobbying industry in the country, various pieces of information are considered, such as the regulatory framework (and relative ‘flaws’), the number of professionals working in the sector, the presence of specific educational pathways (master’s degrees or courses), the presence of professional associations and, if any, of deontological charters or self-disciplinary measures. Overall, an assessment on the degree of professionalisation and development of the industry is formulated, addressing also the perception of lobbyists by the public opinion and the influence of the EU supranational level on the national environment, imagining future scenarios and trends.
Keywords: Political party; International financial reporting standard; Lobbying; Cyprus